2011
DOI: 10.1037/a0021380
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the social and academic competence of economically disadvantaged bilingual preschool children.

Abstract: This longitudinal study was conducted to gain understanding of the social-emotional and academic development of economically disadvantaged bilingual preschool children. In Study 1, the authors combined cognitive, psychosocial, and cultural-linguistic factors to determine profiles of social competence as measured by peer play. A person-centered analysis of 207 Hispanic American preschoolers (ages 4 and 5 years) yielded 6 distinct profiles, 2 of which were socially competent and 1 of which was vulnerable. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 114 publications
4
39
0
2
Order By: Relevance
“…Two more studies can be included in the school readiness and academic achievement category: one that looked at academic achievement as a function of socio-emotional development (Oades-Sese, Esquivel, Kaliski, & Maniatis, 2011) and one that examined counting abilities in bilingual children (Rasmussen, Ho, Nicoladis, Leung, & Bisanz, 2006). Oades-Sese and colleagues (2011) used a longitudinal design and found that low socio-economic Spanish-English bilingual children who were identified as socially competent at age 4 had significantly better academic outcomes than bilingual children who were identified as socially vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…Two more studies can be included in the school readiness and academic achievement category: one that looked at academic achievement as a function of socio-emotional development (Oades-Sese, Esquivel, Kaliski, & Maniatis, 2011) and one that examined counting abilities in bilingual children (Rasmussen, Ho, Nicoladis, Leung, & Bisanz, 2006). Oades-Sese and colleagues (2011) used a longitudinal design and found that low socio-economic Spanish-English bilingual children who were identified as socially competent at age 4 had significantly better academic outcomes than bilingual children who were identified as socially vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of children's social skills is one of the most important outcomes of early childhood education (Gregoriadis, Grammatikopoulos, & Zachopoulou, 2013;Serpell & Mashburn, 2012) because preschoolers' social skills are related to school readiness and adjustment (Denham, 2006;Rimm-Kaufman, Pianta, & Cox, 2000), in order to later succeed in academic achievement (McWayne, Cheung, Green Wright, & Hahs-Vaughn, 2012;Oades-Sese, Esquivel, Kaliski, & Maniatis, 2011) and to peer acceptance (Lindsey, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…According to Tables 3 and 4, it appears that English skills are especially beneficial for communications at school and promote social interactions with peers and teachers whereas heritage language skills are particularly helpful for communications at home and develop family relation quality (Chen & Tse, 2010;Howes et al, 2011;Oades-Sese et al, 2011;Tannenbaum & Howie, 2002). Such divergent results indicate that it is important for future research to consider contexts when investigating relationships between language skills and social competence.…”
Section: Discussion Of Divergent Results Of English and Heritage Langmentioning
confidence: 89%
“…ELLs with lower/the lowest levels of English skills had 1. fewer socio-emotional protective factors in second generation than in first generation (De-Feyter & Winsler, 2009); 2. the lowest level of teacher-rated interpersonal and self-control skills through kindergarten to grade five when compared with peers whose English was native-like and fluent (Han, 2010); 3. lower levels of social interactions and less pretend play at preschools (Howes et al, 2011;Oades-Sese et al, 2011); 4. lower level of teacher-reported assertiveness, interpersonal skills and parent-rated engagement with mothers (Spomer & Cowen, 2001;Winsler et al, 2014); and 5. lower levels of self-worth, peer-rated social interactions (e.g., sociability and cooperation), and teacher and parent reported social competence at schools when they also used less English media use and had fewer associations with native English-speaking friends (Chen et al, 2014;Chen & Tse, 2010).…”
Section: Positive Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation